Using Laser Speckle Contrast Imaging to Quantify Perfusion Quality in Kidney and Pancreas Grafts on Vascular Reperfusion: A Proof-of-Principle Study. Issue 5 (19th April 2023) - Gopal, Jeevan Prakash; Vaz, Osborne; Varley, Rebecca; Spiers, Harry; Goldsworthy, Matthew A.; Siddagangaiah, Vishwanath; Lock, Brian; Sharma, Videha; Summers, Angela; Moinuddin, Zia; van Dellen, David; Augustine, Titus
Abstract : Introduction: The accuracy of intraoperative graft perfusion assessment still remains subjective, with doppler examination being the only objective adjunct. Laser speckle contrast imaging (LSCI) has been used to assess intraoperative blood flow in neurosurgery and in various surgical specialties. Despite its ability to accurately quantify perfusion at the microvascular level, it has not been clinically evaluated in kidney/kidney-pancreas transplantation for perfusion characterization. We aimed to evaluate the utility of LSCI and identify objective parameters that can be quantified at reperfusion. Methods: This study was registered in ClinicalTrials.gov (NCT04202237). The Moor FLPI-2 blood flow imager was used in 4 patients (1 Simultaneous Pancreas and Kidney, 2 deceased, and 1 living donor kidney transplants) during reperfusion to capture reperfusion data. The following parameters were measured: flux (average speed × concentration of moving red blood cells in the sample volume), doppler centroid, total and valid pixels, valid rate, and total and valid area. Flux data were analyzed with Moor FLPI analysis software. Results: The perfusion characteristics and flux images correlated with initial graft function. Conclusions: LSCI is a safe, noncontact imaging modality that provides real-time, accurate, high-resolution, full field blood flow images and a wide range of flux data to objectively quantify organ reperfusion intraoperatively in kidney/kidney-pancreas transplantation. This modality could be used to develop a robust numerical quantification system for the evaluation and reporting of intraoperative organ perfusion, and aid intraoperative decision-making. Perfusion data could be combined with biomarkers and immunological parameters to more accurately predict graft outcomes. Abstract :